SCENARIO PLANNING FOR PT BANGGAI LNG'S BUSINESS STRATEGY TO FACE FUTURE LNG INDUSTRY CHALLENGES - Christian, Rio (Universitas Multimedia Nusantara, 2024)
Abstract- The liquefied natural gas (LNG) industry is undergoing significant transformation due to fluctuating global demand, the transition to renewable energy, and evolving regulations. PT Banggai LNG (PT BLNG), a key player in Indonesia, leverages its strategic location and advanced infrastructure to meet domestic and international demand. However, PT BLNG faces market volatility, intense competition, and increasingly complex environmental regulations. This research employs scenario planning to help PT BLNG develop business strategies to address challenges in the LNG industry, utilizing PESTEL analysis, Porter's Five Forces, VRIO framework, and SWOT analysis. These analyses highlight regulatory pressures, competition, limited resources, and regional demand opportunities. Four strategic scenarios were developed: